Trauma System Support to Facilitate Recovery. (October 2022) - Stinner, Daniel; Hendrickson, Sarah B.; Vallier, Heather A.
Summary: Trauma is a major public health issue. Orthopaedic trauma surgeons are skilled in the acute management of musculoskeletal injury; however, formal training and resources have not been devoted to optimizing recovery after trauma. Recovery entails addressing the biomedical aspects of injury, as well as the psychological and social factors. The purposes of this study were to describe existing programs and resources within trauma centers, developed to promote psychosocial recovery. Supporting research data will be referenced, and potential barriers to program implementation will be discussed. The American College of Surgeons has mandated screening and treatment for mental illness after trauma, which will raise the bar to highlight the importance of these social issues, likely enabling providers to develop new programs and other resources within their systems. Provider education will promote the informing of patients and families, with the intent of enhancing the efficiency and scope of recovery.